Teaching and Learning Methods in Geography Promoting Sustainability - Eija Yli-Panula; Eila Jeronen; Piia Lemmetty (MDPI, 2022)
Understanding and learning geographic knowledge and applying it to sustainable development (SD) depends not only on the knowledge itself, but also on how it is taught and studied. The teaching and learning methods for promoting sustainability in geography have not been thoroughly studied. This qualitative study examined articles on geography teaching and SD. The material was selected using keywords related to geography education. The study describes 17 articles published in peer-reviewed scientific journals from 2008 to 2018. The focus group varied from primary to higher education. The proportion of teaching and learning methods were determined. The data were analyzed using qualitative content analysis. The foci of the analyses were the teaching and learning methods, topics, goals, and levels of thinking skills. Additionally, features of the teaching methods used in geography education, including outdoor education, to achieve the sustainable development goals (SDGs) were investigated. Different teaching methods used together and interactive learning were the most often preferred. Group work and teachers’ presentations were mentioned in 12 articles, and inquiry-based learning and argumentation in half of the articles. The most often written expressions promoting SD in geography education concerned environmental sustainability (42%), followed by social (25%), economic (19%), and cultural sustainability (14%). The most emphasized features of the current teaching methods were active participation, thinking skills, animation, evaluation, dialog, demonstrations, and information and communication technology skills. The whole school approach and forward-looking perspective in geography should be implemented in school education to reach the SDGs and to support SD.